2020
DOI: 10.3389/fsufs.2020.00049
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Sustainability Performance of Typical Conventional and Certified Coffee Production Systems in Brazil and Ethiopia Based on Expert Judgements

Abstract: Increasing consumer awareness on sustainability issues has led to the growing adoption of voluntary sustainability standards in agriculture. This study assesses the sustainability performance of typical conventional and certified coffee production systems in Brazil and Ethiopia based on expert judgements. We apply the SMART-Farm Tool, which represents an operationalization of the SAFA (Sustainability Assessment of Food and Agriculture systems) framework of FAO. Data were collected through expert interviews and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 28 publications
(53 reference statements)
0
20
0
6
Order By: Relevance
“…During workshops with farmers to present assessment results, participants questioned the relevance of several corporate governance indicators for family farms. Similar feedback was observed in applications of SMART-Farm in developing countries, where farming is dominated by smallholder non-commercial farms (Ssebunya et al, 2017, 2019; Winter et al, 2020). One option to address this would be to either omit such indicators or adapt them to the size and organizational context of a farm.…”
Section: Sustainability Performance Of the Swiss Organic Sectormentioning
confidence: 66%
“…During workshops with farmers to present assessment results, participants questioned the relevance of several corporate governance indicators for family farms. Similar feedback was observed in applications of SMART-Farm in developing countries, where farming is dominated by smallholder non-commercial farms (Ssebunya et al, 2017, 2019; Winter et al, 2020). One option to address this would be to either omit such indicators or adapt them to the size and organizational context of a farm.…”
Section: Sustainability Performance Of the Swiss Organic Sectormentioning
confidence: 66%
“…For this study, we reduced the set of indicators from originally over 70 to 56 (Table 2), using only those indicators that were assessed in all six contexts, indicating their relevance in all these contexts. Third, the rating and aggregation of results by an expert panel can insert bias 59 . We argue that the empirical data combined with expert knowledge of a transdisciplinary team provides a chance for less bias than from a single researcher or disciplinary team, aware that aggregation of a complex data set implies the simplification of information.…”
Section: Indicators and Aggregation Of Resultsmentioning
confidence: 99%
“…Similarly, other SAFA-based studies found a poor performance in terms of Accountability and Holistic Management of smallholder farms in developing countries and elsewhere (Landert et al, 2017;Pérez-Lombardini et al, 2021;Schader et al, 2016). A study of noncertified and conventional smallholder coffee farmers in Ethiopia, for example, found that they did not use formal farm monitoring methods (Winter et al, 2020). Poor documentation (e.g.…”
Section: Farm Management and Accountabilitymentioning
confidence: 99%